GERAKAN POLITIK ISLAM HIZBUT TAHRIR DI INDONESIA PADA ERA PASCA REFORMASI - Wijaksono, Agung; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This papper tries to explain political movement of Hizbut Tahrir inIndonesia. HTI is one of the movement's most solid syariah enforcement, neat, andhas an international network.In fact, HTI is also known that the most radical, in a sense, not only foughtto uphold Islamic law but more than that also established the Islamic caliphatebecause according to HTI, the application of Islamic law totaly could not beapplied except within the framework of the caliphate. One of the strategies usedHTI in spreading ideas, a way to controling the strategic arenas in the midst ofsociety.Key word: Islam, politic, Indonesia, Hizbut Tahrir